2022
DOI: 10.3390/ijerph191912945
|View full text |Cite
|
Sign up to set email alerts
|

Food, Energy, and Water Nexus at Household Level: Do Sustainable Household Consumption Practices Promote Cleaner Environment?

Abstract: Governments around the globe are trying to find sustainable solutions for lessening pressure on natural resources and reducing carbon emissions. Daily household consumption of food, energy, and water has an impact on stocks of natural resources, environmental quality, and climate change. Households have significant potential for increasing conservation actions for efficient use of natural resources and greenhouse gas emissions. Households could contribute to a clean and healthy environment by adopting sustaina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 42 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…PHA is a significant category of polymers that has previously been in investigation but is now ready to fully participate in the market, where production capacity is expected to treble in the upcoming few years. Its degradation rate and rubber-like qualities have revealed that it has tremendous opportunities as a replacement for conventional plastics [104,105]. The 2030 Agenda for Sustainable Development-specifically SDG 12, target 12.3-demands for per-capita universal food waste at the retail and consumer levels to half and curtailing the loss of food along production and supply chains.…”
Section: Future Prospectivementioning
confidence: 99%
“…PHA is a significant category of polymers that has previously been in investigation but is now ready to fully participate in the market, where production capacity is expected to treble in the upcoming few years. Its degradation rate and rubber-like qualities have revealed that it has tremendous opportunities as a replacement for conventional plastics [104,105]. The 2030 Agenda for Sustainable Development-specifically SDG 12, target 12.3-demands for per-capita universal food waste at the retail and consumer levels to half and curtailing the loss of food along production and supply chains.…”
Section: Future Prospectivementioning
confidence: 99%
“…Research on food loss and waste began in the late 1980s; since 2005, research on this issue has become more widespread globally [9]. In recent years, research on food waste at the consumer end has mainly focused on five areas; anti-food waste policies and methods [10][11][12][13], quantity measurements of household food waste [14][15][16][17][18], analyses of the harms of food waste [18][19][20], analyses of the factors influencing household food waste [21][22][23][24][25][26], and methods and techniques to deal with food waste [27,28]. In the area of anti-food waste, a study on anti-food waste policies explored the influencing factors of policy implementation and found that the effective implementation of policies is closely related to the active participation of supermarket managers.…”
Section: Introductionmentioning
confidence: 99%
“…A survey examined the role of different sustainable household consumption behaviors in promoting a clean environment in Pakistan, as well as the factors influencing the adoption of these behaviors. The results showed significant relationships between gender, education, residential area, household size, income, and the adoption of sustainable household consumption practices [22]. A study found that households often hold conflicting attitudes toward waste prevention and face a conflict between their willingness to reduce food waste and their preferences for food safety, taste, and freshness [23].…”
Section: Introductionmentioning
confidence: 99%